PEMANFAATAN LIMBAH ORGANIK UNTUK PENINGKATAN KETERAMPILAN DI BIDANG KEWIRAUSAHAAN SANTRI PANTI ASUHAN BAITURRAHMAH MALANG - Anggik Gaguk Ramadan; Jayanti Deya; Notian Notian; Siti Napfiah (JPM PAMBUDI, 2023)
This community service activity was carried out at a children's orphanage called Baiturrahmah Al Amanah Malang. Based on the results of observations by the Baiturrahmah Al-Amanah Orphanage service team, it was found that students studying at junior high and high school levels had a lot of free time, this was because the school schedule was not too busy and the lack of activities made the students more productive. In fact, the Baiturrahmah Al-Amanah Orphanage has the potential for natural resources that can be developed into marketable products so that it can become a forum for students to improve their skills and increase the orphanage's income. The implementation of this service activity was carried out by students proposing PKM-PM. The activity begins with observing partners and coordinating with the parties concerned. Technical training activities were carried out for 5 months starting from preparation to evaluation. Meanwhile, the technical implementation of production includes the stages of cleaning, soaking, drying the water hyacinth, and the product manufacturing process. Next is the packaging and marketing training process. The final service activity is the evaluation of all activities that have been carried out. Based on the activities carried out, the partners gave a very positive response because this activity could improve the skills of the orphanage students